2016
DOI: 10.1097/mej.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Optimal chest compression rate in cardiopulmonary resuscitation: a prospective, randomized crossover study using a manikin model

Abstract: The number of high-quality CPR compressions was the highest at a compression rate of 120 min, and increased incomplete recoil occurred with increasing compression rate. However, further studies are needed to confirm the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In a study published in 2016, Lee et al [34] analyzed metronome-guided adult continuous chest compressions with the metronome set to 100, 120, 140, and 160 bpm, in a random order. They revealed that the share of incomplete chest recoils was lower at the rates of 100 and 120 CPM as compared with 160 CPM.…”
mentioning
confidence: 99%
“…In a study published in 2016, Lee et al [34] analyzed metronome-guided adult continuous chest compressions with the metronome set to 100, 120, 140, and 160 bpm, in a random order. They revealed that the share of incomplete chest recoils was lower at the rates of 100 and 120 CPM as compared with 160 CPM.…”
mentioning
confidence: 99%
“…The incremental increase in the CCR to a maximum of 150/min exceeds recommendations and has the potential to limit full recoil and cardiac filling. 31 We have previously published that a faster CCR favoured increased ETCO 2 levels while a slower CCR favoured increased DBP levels. 24 In one clinical study, neither DBP nor survival to hospital discharge differed between children who received a CCR >140/min or 100–120/min.…”
Section: Discussionmentioning
confidence: 92%
“…Chest compression depth can affect ETCO 2 levels, 13 and changes to the CCR can affect chest compression depth. 31 It is possible that unintentional differences in the depth of chest compressions, in addition to changes to the CCR and EAI, contributed to improved survival and haemodynamics in the algorithm group. We used CPR coaches in an attempt to maintain similar compression depth, but neither compressors nor coaches could be blinded to group assignment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Zou et al [29] studies indicate that the optimal rate of chest compression is 120/min. Studies published by Lee et al [30] also indicate 120 CPM as the optimal chest compression rate, while noting that higher compression rates can reduce chest relaxation. Similar conclusions can also be drawn from studies by Smereka et al [8], as well as from studies by other authors [31][32][33].…”
Section: Discussionmentioning
confidence: 95%